Comparing illness duration and age as predictors of treatment outcome in female inpatients with anorexia nervosa. Issue 3 (4th May 2023) - Meule, Adrian; Kolar, David R.; Rauh, Elisabeth; Voderholzer, Ulrich
ABSTRACT: It has been widely assumed that longer illness duration predicts poorer treatment outcome in persons with anorexia nervosa (AN). However, studies on the prognostic effects of illness duration have produced mixed results. Thus, the aim of the current study was to examine the relationship between illness duration and short-term treatment outcome in a large sample of female inpatients with AN ( n = 902, aged 12–73 years). Treatment outcome variables included body mass index, therapist-rated global functioning (Global Assessment of Functioning scale and Clinical Global Impression–Improvement scale) and subscales of the Eating Disorder Inventory–2. Longer illness duration predicted smaller weight gain, smaller improvements in global functioning, and smaller decreases in self-reported eating disorder symptoms. However, illness duration was almost perfectly correlated with patients' age ( r = .81, 95% CI [.76, .85]), and comparing regression models revealed that models using either illness duration or age were indistinguishable. Results suggest that longer illness duration does indeed relate to worse short-term treatment outcome in inpatients with AN. This effect, however, does not add significant information above and beyond patients' age and, thus, the importance of illness duration for anticipating treatment outcome both in research and in clinical practice must be critically examined.